(untitled) (International Journal of Fine, Performing and Visual Arts, ISSN: 3006-6581, 2023)
The abstract provides a concise summary of the research paper, "The Influence of Colonial Art Education on Indigenous Art Practices: Case Studies from the Pacific Islands." This study investigates the impact of colonial-era art education on the artistic practices of indigenous communities in the Pacific Islands. The research employs case studies to delve into specific instances and contexts, aiming to unveil the multifaceted relationship between colonial art education and traditional indigenous art. The paper explores how Western-centric art education introduced during the colonial period has influenced and shaped the artistic expressions of Pacific Islander communities. By examining various case studies, the research sheds light on the complexities of this influence, considering factors such as cultural adaptation, resistance, hybridization, and the preservation of indigenous artistic traditions.